Concomitant extraction process of niobium at the titanium tetrachloride production - Sarsembekov, Т.К.; Yanko, Т.B.; Sidorenko, S.A.; Pylypenko, M.M. (Вопросы атомной науки и техники, 2020)
Development of the fundamentals of a technology for producing niobium by the concomitant extraction in the process of production of titanium tetrachloride from titanium raw materials. The paper provides data on the amount of niobium contained in the feedstock to produce titanium tetrachloride, the distribution of niobium during processing by products and waste. The forms of phase transformations and transitions of niobium during processing are considered. Schemes for processing niobium-containing chloride materials and technologies for their further application for producing alloys for nuclear power are proposed. Розроблено основи технології одержання ніобію шляхом попутного вилучення в процесі виробництва тетрахлориду титану з титанової сировини. У роботі наведено дані про кількість ніобію, що міститься у вихідній сировині для виробництва тетрахлориду титану, розподіл ніобію в процесі переробки за продуктами і відходами виробництва. Розглянуто форми фазових перетворень і переходи ніобію в процесі переробки. Запропоновано схеми переробки хлоридних матеріалів, що містять ніобій, і технології їх подальшого застосування для отримання сплавів для ядерної енергетики. Разработаны основы технологии получения ниобия путем попутного извлечения в процессе производства тетрахлорида титана из титанового сырья. В работе представлены данные о количестве ниобия, содержащегося в исходном сырье для производства тетрахлорида титана, распределение ниобия в процессе переработки по продуктам и отходам производства. Рассмотрены формы фазовых превращений и переходы ниобия в процессе переработки. Предложены схемы переработки ниобийсодержащих хлоридных материалов и технологии их дальнейшего применения для получения сплавов для ядерной энергетики.